2008
DOI: 10.1002/cphc.200700742
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin Nanocavity Caging Effect on Electronic Dephasing

Abstract: The ability to control molecular wavefunctions may lead to novel quantum technologies, such as bond-selective chemistry and quantum computing. [1][2][3] An understanding of the coherent-loss process is essential for the realization of these quantum technologies using quantum-interference (QI) effects in condensed media. Although the overwhelming majority of chemical reactions take place in solution, there have been very few experimental studies on the coherent reaction control of polyatomic molecules in conden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Taking into account the spectral line shape of absorption (which turns out to be a Voigt profile when both the homogeneous contribution with Lorentzian line shape as well as the inhomogeneous contribution with Gaussian line shape are present) and laser pulse (Gaussian profile), the QI signal under periodically phase-modulated pulse-pair excitation has shown to be varied for two different scenarios [13]: (1) if the pulse spectral width is at least an order of magnitude larger than the absorption linewidth, one expects the fringe frequency to be the inverse of the frequency width of the absorption profile and (2) at the other extreme, if a narrow pulse spectrum excites a subpopulation of the broad inhomogeneous absorption line shape, then the temporal fringe oscillations occur at a pulse carrier-wave frequency analogous to ultrafast hole-burning experiments [9,32]. For an intermediate situation (which happens to be the case in our experiment), the QI signal is neither given by the inverse of the spectral width nor follows the optical field oscillations [13,14]; for partial pulse-pair overlapping zone the QI signal differs from optical field oscillations due to nuclear dynamics i.e. vibrational WPI also [12].…”
Section: Methodsmentioning
confidence: 74%
See 2 more Smart Citations
“…Taking into account the spectral line shape of absorption (which turns out to be a Voigt profile when both the homogeneous contribution with Lorentzian line shape as well as the inhomogeneous contribution with Gaussian line shape are present) and laser pulse (Gaussian profile), the QI signal under periodically phase-modulated pulse-pair excitation has shown to be varied for two different scenarios [13]: (1) if the pulse spectral width is at least an order of magnitude larger than the absorption linewidth, one expects the fringe frequency to be the inverse of the frequency width of the absorption profile and (2) at the other extreme, if a narrow pulse spectrum excites a subpopulation of the broad inhomogeneous absorption line shape, then the temporal fringe oscillations occur at a pulse carrier-wave frequency analogous to ultrafast hole-burning experiments [9,32]. For an intermediate situation (which happens to be the case in our experiment), the QI signal is neither given by the inverse of the spectral width nor follows the optical field oscillations [13,14]; for partial pulse-pair overlapping zone the QI signal differs from optical field oscillations due to nuclear dynamics i.e. vibrational WPI also [12].…”
Section: Methodsmentioning
confidence: 74%
“…An alternative way to retrieve coherent dynamics is by making use of the statistical variance of interferometric noise following randomly phased pulse-pair excitation (known as coherence observation by interference noise, or COIN) [9,10]. In contrast, here we report selective enhancement or suppression of fluorophores based on direct observation of the QI signal only [12][13][14], without any deliberate attempt to unravel pure coherent dynamics.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…In another word, protection of molecular wavefunctions from the surrounding environment becomes important issue for realization of quantum control techniques in condensed phases. For that purpose, we aimed for the protection of the quantum phase of a guest molecule using the size-fit nano-space in a cyclodextrin nanocavity (Kiba et al, 2008). Cyclodextrins (α-, β-, or γ-CD), which are oligosaccharides with the hydrophobic interior and the hydrophilic exterior, are used as nanocavities because of their unique structures and the fact that six(α-), seven(β-), or eight(γ-) D-glucopyranose units determine the sizes whose diameters are ~5.7, 8.5, and 9.5 Å, respectively.…”
Section: Cyclodextrin Nanocavity Caging Effect On Electronic Dephasinmentioning
confidence: 99%
“…In our previous study, we reported the moderation of electronic decoherence of perylene in -CD aqueous solution at room temperature, as measured by an optical-phase-controlled pulse-pair quantum interferometer, combined with spectral lineshape analysis [16]. Interactions between guest molecules and surrounding environment are the origin of the electronic decoherence.…”
Section: Introductionmentioning
confidence: 99%